Investigating the conditions for psychological momentum in the field: Evidence from men`s professional tennis - Meier, P.; Flepp, R.; Rüdisser, M.; Franck, E. P. (SSRN, 2019)
We examine how interruptions and personal and contextual factors affect the manifestation of psychological momentum (PM). Using men`s singles tennis point-by-point data from the two Grand Slam tournaments, Wimbledon and Roland Garros, between 2009 and 2014 (N=29,934), we employ realized break points as the potential triggers of PM and rest periods between two sequential games as the exogenous task interruptions. Controlling for player ability and the state of the match, we find that players are more likely to win the next game after realizing a break point only if there is no rest period between games. Thus, our results suggest that interruptions terminate the momentum effect. Furthermore, we find that the effect of PM increases for players with a lesser relative ability and at a later stage within a match, showing the importance of personal and contextual factors for PM.